المعنى الحقيقي لمفهوم التخطيط الاستراتيجي للموارد البشرية انطلاقاً من موقعه على هيراركية الاستراتيجية (التدرج الهرمي لاستراتيجية المنظمة). - عواد, يونس; رجب, حيدرة (Latakia University Journal - Economic and Legal Sciences Series, 2014)
يهدف هذا البحث بشكل أساسي إلى توضيح المعنى الحقيقي لمفهوم التخطيط الاستراتيجي للموارد البشرية من خلال تسليط الضوء على الحالات أو الأدوار التي ترسم المنحى والاتجاه العام لأهمية ومكانة الدور الذي تأخذه عملية تنفيذ أو تكوين استراتيجية الموارد البشرية في المنظمة على خارطة هيراركية الاستراتيجية. حيث اعتمد هذا البحث على المنهج النوعي الذي يركز بطبيعته على الفهم العميق لمعنى معين (مفهوم معين) أو وصف حالة معينة أو ظاهرة معينة أو حتى مشكلة أو حدث معين أكثر من تركيزه على تفسير نتائج معينة، ومن خلال عملية مسح أدبي شامل لخصائص حالات استراتيجية الموارد البشرية في المنظمة وتعميق مفاهيمها وخلص هذا البحث إلى مايلي: تتحقق شروط عملية التخطيط الاستراتيجي للموارد البشرية عند تنفيذ وتكوين استراتيجية الموارد البشرية على مستوى المنظمة ككل باعتبارها الاستراتيجية النهائية التي يجب أن تتكيف معها وتدعهما الاستراتيجيات الأخرى كافة في المنظمة. يطلق على إجراءات تنفيذ وتكوين استراتيجية الموارد البشرية في المنظمة على المستوى التشغيلي عندما تكون استراتيجية تابعة وداعمة ومتكيفة وفق متطلبات استراتيجية الأعمال التنافسية في المنظمة بالتسيير الاستراتيجي للموارد البشرية. تعبر عملية تخطيط الموارد البشرية بشكل استراتيجي عن صياغة الاستراتيجية الخاصة بعملية تخطيط الموارد البشرية كإحدى وظائف إدارة الموارد البشرية التنفيذية على المستوى التكتيكي ضمن سياق منظور استراتيجية المنظمة النهائية. Basically, this research aims to clarify the true meaning of the concept of strategic planning for human resources by highlighting the cases or roles that shape the orientation and general direction of the importance and status of the role played by the process of implementation or configuration strategy of human resources in the organization of the hierarchy strategy map. A qualitative approach that focuses inherently to discovering meaning has been used, giving explanations and describing the situation, phenomenon, and problems, rather than interpreting certain results. Through an extensive literature survey of the characteristics of human resources strategy in the organization and the process of deepening the concepts, this research shows the following: Terms of the process of strategic planning for human resources are realized when the implementation or configuration of human resources strategy is done, as a final strategy, at the level of the organization as a whole, which must adapt to and be supported by all the other strategies of the organization. We call the procedures for the implementation and configuration strategy for human resources in the organization at the operational level supportive strategies adapted to the requirements of a competitive business strategy in the organization by "Strategic Steering of Human Resources”. As for the concept of strategic human resource planning, it is the process of expressing private strategy formulation process of human resource planning as one of the functions of traditional human resource management at the tactical level within the context of the organization's strategic perspective as a whole.